Clinical attachment loss and its association with risk indicators in Brazilian adolescents and young adults - Cortelli, José Roberto; Cortelli, Sheila Cavalca; Aquino, Davi Romeiro; Roman-Torres, Caio Vinícius Gonçalves (Brazilian Dental Science, 2010)
Purpose: This cross-sectional study aimed to determine the prevalence of periodontal clinical attachment loss in 622Brazilian adolescents and young adults (15 to 25 years) and its correlation with age, gender and smoking habits. Inaddition, to evaluate the influence of different cut-off points on the prevalence data. Materials and Methods: full-mouthperiodontal examination was conducted by two trained and calibrated examiners to measure periodontal probing depth(PPD) and clinical attachment level (CAL) at 6 sites per tooth using a manual periodontal probe. The data analysiswas performed in a subject level according to three cut-off points (CAL ≥ 1mm, 2mm or 3mm). Statistical analysiswas conducted using Wilcoxon, Student-t and Mann Whitney tests (p < 0.05). The association between age and CALwas also analyzed by OR calculation. Results 454 subjects presented CAL of 1mm, 341 of 2mm and 251 of 3mm. Ineach cut-off point it was not observed significant differences between males and females, neither between smokers andnon-smokers. Only age was associated with CAL. Subjects aged 20-25 years were 2.92 times more likely to have 2mmof CAL than subjects 15-19 years old. Conclusions:In this young population gender and smoking habits did not showassociation with CAL instead-off, age revealed an association with both presence and severity of CAL. Different cut-offpoints of periodontal disease influenced prevalence data in a significant way.